Superchaotropic Boron Clusters as Membrane Carriers for the Transport of Hydrophilic Cargos - Hu, Xin‐Yue; Guo, Dong‐Sheng (Angewandte Chemie International Edition, 2022)
Design of membrane transporters is important in pharmaceutical drug delivery and bioimaging. Traditionally, the amphiphilic transport mechanism has governed the design of membrane carriers over the last 50 years. Recently, Montenegro, Nau and co‐workers discarded classical amphiphilic models and proposed a new transport principle based on the chaotropic effect. They utilized globular boron clusters as membrane carriers to transport a broad range of hydrophilic cargo. Herein, we highlight this recent pioneering work, which is a landmark for membrane transport. Montenegro, Nau and co‐workers abandoned the typical amphiphilic model of membrane transport and proposed a new chaotrope‐mediated transport principle. They utilized superchaotropic boron clusters as membrane carriers to transport a broad range of hydrophilic cargo. This groundbreaking work is a conceptual innovation and may have a profound impact on cell‐biological, neurobiological, physiological, and pharmaceutical studies.